Association between vancomycin therapeutic drug monitoring and improved clinical outcomes in critically ill patients receiving renal replacement therapy: a retrospective cohort study - Peng, Huaidong; Tang, Xiaomei; Chen, Lijin; Yang, Qilin; Cai, Jinliang; Xie, Tingting; Xu, Dan (Frontiers in Pharmacology, 2026)
IntroductionVancomycin is commonly prescribed for serious infections in critically ill patients. A substantial proportion of these individuals present with renal impairment or develop acute kidney injury (AKI), and some may require renal replacement therapy (RRT). Different RRT modalities can substantially affect vancomycin pharmacokinetics, thereby posing challenges for individualized dosing. Although therapeutic drug monitoring (TDM) is recommended by clinical guidelines to optimize drug exposure, its association with mortality among critically ill patients undergoing RRT has not been well characterized.MethodsThis retrospective study used the MIMIC-IV database to identify adults with an initial ICU admission who received RRT within the first week and intravenous vancomycin during the ICU stay. Patients were classified into TDM and non-TDM groups according to whether TDM was performed. The primary outcome was 30-day all-cause mortality. To control for confounding, baseline characteristics were balanced using inverse probability of treatment weighting (IPTW) based on propensity scores. Associations between TDM and mortality were assessed using IPTW-weighted Cox regression, with results compared to unweighted Cox models. Subgroup analyses stratified by clinical characteristics and RRT modalities were performed to explore effect heterogeneity. Sensitivity analyses addressing missing cumulative vancomycin dose were conducted using random forest imputation, complete-case analysis, and the missing-indicator method.ResultsA total of 2,085 patients were included, with 1,556 in the TDM group and 529 in the non-TDM group. 30-day mortality was significantly lower in the TDM group (38.9% vs. 48.8%, P < 0.001). Multivariable Cox regression analyses, both before and after IPTW adjustment, demonstrated a consistent association between TDM and reduced mortality risk (hazard ratio [HR] 0.457–0.478, all P < 0.001). Kaplan–Meier analysis further confirmed higher survival in the TDM group (log-rank P < 0.001). In the continuous renal replacement therapy (CRRT) subgroup, all models yielded consistent results, with TDM associated with significantly lower mortality (HR 0.427–0.431, all P < 0.001). Sensitivity analyses supported the robustness of these findings, as the inverse association between TDM and mortality persisted across all approaches to handling missing vancomycin dose data (HR 0.474–0.610, all P < 0.001).ConclusionVancomycin TDM was significantly associated with reduced 30-day mortality in critically ill patients receiving RRT, with an even stronger effect observed in those undergoing CRRT. These findings support the potential clinical relevance of TDM in this high-risk population.